The Effect of Work Posture, Work Load, and Psychosocial Factors on Work Fatigue in Forklift Drivers in the Warehouse Department of PT Y - Hidayat, Muh. Taufiq; Erislan, Erislan; Ramli, Soehatman; Sugiarto, Sugiarto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to evaluate the extent to which work posture, workload intensity, and psychosocial aspects affect fatigue levels in forklift operators at PT Y's warehouse. The background of this study is the high incidence of property damage involving forklifts and changes in storage systems that increase operator workload. This study uses a quantitative approach with PLS-SEM-based regression analysis. The results of the analysis show that all three factors—work posture, workload, and psychosocial conditions—have a significant and positive effect on work fatigue, with regression coefficients of 0.358; 0.367; and 0.333, respectively. The T-statistic value of all three exceeds 1.96 and the P-value <0.05, indicating that all three are statistically significant. These findings indicate that non-ergonomic work positions, heavy workloads, and unfavorable psychosocial conditions can increase the risk of work fatigue. This study recommends the need for in-depth ergonomic evaluations, reorganization of operational rhythms, and strengthening social interactions in the workplace to reduce fatigue levels and prevent potential work accidents.